Perubahan Capital Aset Pricing Model, Risiko, dan Efisiensi: Triger Unit Asuransi Full-Pledge Syariah - Arianty, Erny; Ghoni, Abdul (Jurnal Ilmiah Ekonomi Islam, 2024)
Abstract This research aims to analyze changes in capital asset values, risk levels, and efficiency as triggers for sharia insurance units to immediately provide full sharia guarantees. The method used is a quantitative method using financial ratios, Capital Asset Price Model (CAPM), and Financial Ratios. CAPM is used to find stock returns, financial ratios for risk and level of return. The results show that there is a change in PT JMAS stock returns which shows a decline in value. Regarding risk mitigation, the third company demonstrated effective risk control. Jasindo is bolder in taking premium risks, but the company has a strategy to increase the percentage of claims that become liabilities to reinsurance companies. In contrast to the Askrida sharia which is more careful in choosing premiums with high risks, this results in claims values that are relatively low and continue to decline. Finally, only the Askrida Syariah company shows a stable value even though the size is not yet significant. ROA growth at Jasando Syariah is less stable in maintaining returns from the use of its assets. There were less stable changes in ROA during 5 periods, 2017, 2018, 2019, 2021 and 2022..